Excavations of Kytaion’s Southwestern Suburb in 2019–2022 - Khrshanovskiy , Vladimir (Hyperboreus, 2024)
The article summarizes the results of the security and rescue works of the Kytaion archaeological expedition of the Institute of Archaeology RAS in the area of coastal erosion of the Bosporan city of Kytaion in 2019–2022. The study of this section has been conducted since 2016 in two excavation areas – XLVI and XLVII. In excavation area XLVI, in addition to the previously studied unearthed ritual and memorial complexes, two more ritual pits nos. 389 and 393, the ritual complex no. 400, and the grave without inventory no. 398 have been excavated. In accordance with the formerly determined archaeological context, they are attributed to the same Late Antique age – the 4th–5th centuries AD. Besides 5 graves, more than 10 ritual pits and at least 2 ritual grounds with the remains of funeral feasts and sacrifices and many primitive stone altar constructions were found in this excavation area. The size of the unearthed complex allows us to presume that it was the sanctuary combined with the necropolis. In the same years in excavation area XLVII, the second ash hill no. 396 was found and one more pit no. 397 was unearthed. After this discovery, all finds from the excavation area can be considered to be offerings, linked to the rituals performed on the two ash hills and near the ritual pits. As before, asynchronous material from the 4th century BC to the 1st–3rd centuries AD, along with many animal bones, was found in the excavation areas XLVI and XLVII.